PERBEDAAN PERSEPSI MAHASISWA MENGENAI KOMPETENSI DOSEN TERSERTIFIKASI (Studi Pada Mahasiswa Prodi Pendidikan Akuntansi IKIP PGRI MADIUN) - Elva Nuraina; Nik Amah (JURNAL PENDIDIKAN AKUNTANSI, 2014)
This study aims to determine the differences in students perceptions regarding the competence of certified lecturer. The study was conducted on students of Accounting Education department IKIP PGRI MADIUN with samples of 80 students. Sampling technique done by proportional random sampling. Determination of the number of samples generated using a quota sample and 80 students. Data was collected through a questionnaire instrument, while the data analysis done by one way analysis of variance (one way ANOVA). The results showed that there were no differences perceptions of student in class 2010, 2011, 2012, and 2013 with regard to certified lecturer competence.